Soft rock tunnel construction method
Patent Information
- Application Number
- CN202610840788.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-10-16
AI Technical Summary
当围岩含水率较低时,采用双液浆可能导致不必要的材料浪费;当含水率较高时,单液浆的防渗效果不足,易造成渗漏水或围岩失稳
本发明通过围岩含水率实时监测与临界含水率标定,实现了分级注浆决策(固结型单液浆或防渗型双液浆),显著提升了注浆针对性与围岩稳定性,拱顶沉降和周边收敛远低于允许值,变形稳定周期缩短约50%;利用软岩弃渣制备可控低强度回填材料并高压回填初期支护背后空隙,使填充率达到95%以上,空洞发生率由20%~30%降至3%以下,实现了弃渣100%就地资源化利用;采用锚杆二次张拉与微膨胀砂浆注浆技术,预紧力损失率由30%~50%降至8%以下,锚杆尾部加强套双面满焊使抗拉承载力提升一倍以上,显著增强了锚固系统的长期耐久性;针对临界含水率附近的过渡区间加密小导管并采用适中配比双液浆,每延米注浆成本降低约12%;对取样困难地层提供旁压或波速间接确定临界含水率的方法,标定周期由5~7天缩至1天以内,偏差小于±0.5%;通过调控双液浆凝胶时间及对高渗透地层采用增粘剂+间歇注浆,有效防止浆液流失,注浆量减少30%,帷幕渗透系数达标;增加回填材料浸水强度保留率检验及粉煤灰等量替代方案,保障了不同原料条件下的长期水稳性;预埋排气管并采用地质雷达与钻孔取芯组合检测,确保回填密实度;明确二次衬砌施作时机及排水盲沟位于防渗帷幕内侧边缘,避免了衬砌开裂和过度排水。综合而言,本发明实现了软岩隧道施工的高质量、低成本、环保化和高可靠性。
Abstract
Description
Technical Field
[0001] This invention relates to the field of tunnel engineering. More specifically, this invention relates to a method for constructing soft rock tunnels. Background Technology
[0002] In soft rock tunnel engineering, the surrounding rock often exhibits properties such as softening, disintegration, and expansion upon contact with water. Existing construction methods have the following problems: First, changes in the moisture content of the surrounding rock have a significant impact on tunnel stability, but dynamic monitoring and quantitative assessment of the moisture content are often lacking during construction. Pre-grouting is often implemented based on experience or fixed parameters, failing to select different grouting materials and processes according to variations in moisture content. When the moisture content of the surrounding rock is low, using a two-component grout may lead to unnecessary material waste; when the moisture content is high, a single-component grout is insufficient for seepage prevention, easily causing water leakage or surrounding rock instability. How to scientifically select a grouting scheme based on real-time moisture content remains an unresolved problem in engineering.
[0003] Secondly, tunnel excavation generates a large amount of soft rock waste. The conventional method of disposal is off-site transportation, which not only increases transportation costs and land occupation, but also fails to utilize the engineering properties of the waste. Some projects have attempted to use the waste for backfilling, but the lack of control over the strength, fluidity, and long-term water stability of the backfill material has led to incomplete backfilling or softening later on. This can easily create voids between the initial support and the surrounding rock, which in turn can cause lining cracking.
[0004] Third, in anchor bolt support, the hardening and shrinkage of ordinary cement mortar leads to a significant loss of preload, and the welded connection strength between the anchor bolt tail and the steel arch is insufficient, resulting in a decline in anchoring effectiveness after long-term service. Traditional single-tensioning methods cannot guarantee the effective maintenance of preload.
[0005] Fourth, in the transitional range where the moisture content is close to the critical value, the single grouting mode has poor adaptability; in high-permeability fractured strata, the two-component grout is prone to loss, making it difficult to establish grouting pressure; in areas where undisturbed core sampling is difficult, the critical moisture content is difficult to calibrate, affecting the implementation of staged grouting. In addition, insufficient air venting at the arch during backfill grouting, lack of reliable testing methods for filling effect, unclear timing of secondary lining construction, and neglect of the coordination between the drainage system and the grouting curtain are all common technical problems affecting the construction quality and safety of soft rock tunnels. Summary of the Invention
[0006] One object of the present invention is to solve at least the above-mentioned problems and to provide at least the advantages that will be described later.
[0007] To achieve these objectives and other advantages of the present invention, a method for constructing soft rock tunnels is provided, comprising the following steps: S1. Dynamic monitoring and threshold calibration of surrounding rock moisture content: In the surrounding rock of the excavated section behind the tunnel face and the unexcavated section in front, moisture content sensors are deployed at longitudinal intervals of 5-10m, and the volumetric moisture content ω of the surrounding rock is continuously monitored using the time-domain reflectometry method. Uncirculated soft rock cores are taken from the tunnel site for permeability and expansion tests under different moisture content conditions, with the surrounding rock permeability coefficient K ≥ 1 × 10⁻⁶. -5 The minimum moisture content corresponding to a free expansion rate δ ≥ 5% is taken as the critical moisture content ω. c If sufficient rock cores cannot be obtained on site, then take ω. c =25% is the default value; S2. Advanced curtain grouting based on moisture content classification: When the real-time monitored ω≤ω c When the surrounding rock is determined to be in a medium water content state, the first grouting mode is implemented: drill advanced small guide pipes with an outward insertion angle of 10°~15° along the radial direction of the tunnel. The length of the small guide pipes is 3~5m and the circumferential spacing is 0.8~1.2m. Ordinary silicate cement single-liquid grout is injected into the surrounding rock through the small guide pipes. The water-cement ratio is 0.8:1~1:1 and the grouting pressure is 0.5~1.0MPa, forming a consolidated curtain grouting ring with a thickness of not less than 2.5m. When the real-time monitored ω>ω c When the surrounding rock is determined to be in a high water content or water-rich state, the second grouting mode is executed: Similar to the first grouting mode, a pre-drilled small guide pipe is installed, but a cement-water glass dual-liquid grout is injected. The water-cement ratio of the cement grout is 0.8:1~1:1, the Baume degree of the water glass grout is 30~40°Bé, the volume ratio of cement grout to water glass grout is 1:0.6~1:0.8, and the grouting pressure is 1.0~1.8MPa, forming a seepage-proof curtain grouting ring with a thickness of not less than 3.5m, and the permeability coefficient of this seepage-proof curtain grouting ring is ≤1×10⁻⁶. -6 cm / s; S3. Staged excavation and initial support of the tunnel: After the pre-curtain grouting is completed and the grout gel time reaches the set value, the tunnel is excavated in stages using the step method, with each cycle advancing ≤0.8m; immediately after excavation, C25 grade or higher concrete is sprayed and I-beam arch frames are erected to form the initial support structure; S4. Waste slag is modified into controllable low-strength backfill material: The soft rock waste generated in step S3 is crushed and screened to a particle size ≤3mm; it is mixed according to the mass ratio of waste:cement:fly ash:early strength water-reducing agent = 1:(0.12~0.18):(0.05~0.10):(0.01~0.02), and 15%~20% water of the total solid mass is added. The mixture is stirred until the slump is 80~120mm to obtain a controllable low-strength backfill material with a 28-day unconfined compressive strength of 0.5~1.5Mpa. S5. Backfilling behind initial support: After the initial support structure is completed and reaches more than 70% of the design strength, backfill grouting holes are reserved or drilled on the surface of the initial support. The controllable low-strength backfill material obtained in step S4 is injected into the gap between the initial support structure and the surrounding rock through grouting equipment at a pressure of 0.2~0.4MPa until grout continuously flows out of the vent hole and the grouting pressure is stable at more than 0.3MPa for 2 minutes. Grouting is then stopped, so that the gap filling rate is ≥95%. S6: Anchor bolt secondary tensioning and locking: Hollow grouting anchors are drilled and installed within a 120° range of the tunnel arch and at the waist positions on both sides. The anchors are 4-6m long and spaced 1.0m x 1.0m apart. After the anchors are inserted into the surrounding rock, an initial pre-tightening force of 50kN is applied. Then, M30 cement mortar is injected through the center hole of the anchor at a grouting pressure of 1.0-1.5MPa. After the grout reaches the design strength, a second pre-tightening force is applied to the anchors to achieve a final pre-tightening force of 80-100kN. The tail of the anchor is then welded and fixed to the steel arch frame of the initial support.
[0008] Preferably, in S2, when the real-time monitored ω and ω c When the absolute value of the difference is ≤2%, a transitional grouting mode is implemented: the circumferential spacing of the advanced small guide pipes is increased to 0.6~0.8m, and cement-water glass double-liquid grout with a volume ratio of 1:0.5 is injected. The grouting pressure is taken as the average value of the first and second grouting modes; the water content sensor is buried at a depth of 1.5~3.0m within the surface of the surrounding rock, with no less than 4 measuring points evenly arranged circumferentially; for cross-sectional areas >80m² 2 For large-section tunnels, the longitudinal monitoring interval is 5m, and the number of circumferential monitoring points is increased to 8.
[0009] Preferably, when it is difficult to obtain undisturbed soft rock core samples or when the disturbance is too great, ω is indirectly determined by using a pressure meter test or in-hole wave velocity test. c ω is defined as the moisture content corresponding to when the lateral pressure modulus E0 decreases to 60% of its natural state. c Or with shear wave velocity V x The moisture content that decreases to 70% of its natural state is taken as ω. c .
[0010] Preferably, in the second grouting mode of S2, the gel time of the cement-water glass dual-liquid grout is controlled between 30 and 90 seconds, which is achieved by adjusting the Baume degree of the water glass or by adding 0.2% to 0.5% of disodium hydrogen phosphate retarder by the mass of cement; when the permeability coefficient of the surrounding rock K ≥ 1 × 10 -4 When the flow rate is cm / s, 0.5% to 1.5% of calcium lignosulfonate or polyacrylamide by weight of cement is added to the two-component grout, and intermittent grouting is adopted.
[0011] Preferably, in S4, the controllable low-strength backfill material also needs to undergo a water immersion compressive strength test: after the standard curing period of 28 days, the unconfined compressive strength of the specimen after immersion in water for 48 hours should not be less than 80% of that in the dry state; if this is not met, then 5% to 10% bentonite or 2% to 4% silica fume should be added according to the cement mass; when fly ash is unavailable, it should be replaced with an equal amount of finely ground slag powder or natural zeolite powder.
[0012] Preferably, in S5, PVC exhaust pipes with an inner diameter of 20-30mm are pre-embedded at the arch crown and the two sides of the arch waist of the initial support structure, and ball valves are installed at the outlet end; when backfilling and grouting, the valves are opened first, and after grouting is continuously discharged without air bubbles, the valves are closed and grouting continues until the pressure is stable; the filling rate is tested by core drilling or ground-penetrating radar, and a test section is set every 10-20m. If the core sample shows complete backfill material without continuous voids, or the porosity calculated by the ground-penetrating radar reflected wave amplitude is ≤5%, it is considered qualified.
[0013] Preferably, in S6, 8%~12% of UEA expansion agent or 5%~8% of aluminum powder paste by weight of cement is added to M30 cement mortar to control the volume expansion rate at 0.02%~0.05%; when welding the tail of the anchor rod to the steel arch frame, a 10cm long thick-walled steel pipe reinforcing sleeve is first fitted, and after the reinforcing sleeve is threaded to the anchor rod, it is fully welded to the steel arch frame on both sides, with a weld height ≥6mm, and anti-corrosion treatment is performed.
[0014] Preferably, it also includes: S7. After the anchor bolts are locked with secondary pre-tightening force, and the tunnel deformation monitoring shows that the arch settlement rate is <0.2mm / day for 5 consecutive days and the perimeter convergence rate is <0.1mm / day for 5 consecutive days, the secondary lining shall be constructed with concrete strength ≥C30 and thickness ≥30cm. Before construction, longitudinal drainage blind ditches shall be set at the foot of the walls on both sides of the tunnel, and transverse drainage pipes shall be set every 10m. The drainage blind ditches shall be located at the inner edge of the anti-seepage curtain grouting ring.
[0015] The present invention has at least the following beneficial effects: This invention achieves graded grouting decision-making (consolidated single-liquid grout or anti-seepage double-liquid grout) through real-time monitoring of surrounding rock moisture content and calibration of critical moisture content, significantly improving grouting targeting and surrounding rock stability. The crown settlement and perimeter convergence are far below allowable values, and the deformation stabilization period is shortened by approximately 50%. Controllable low-strength backfill material is prepared using soft rock waste and high-pressure backfilled behind the initial support voids, achieving a filling rate of over 95% and reducing the void occurrence rate from 20%~30% to below 3%, realizing 100% on-site resource utilization of waste. The use of secondary anchor tensioning and micro-expansion mortar grouting technology reduces the preload loss rate from 30%~50% to below 8%, and the double-sided full welding of the anchor tail reinforcement sleeve more than doubles the tensile bearing capacity, significantly enhancing the long-term durability of the anchoring system. For critical moisture content... By using denser conduits and appropriately proportioned two-component grout in the transition zone near the water content, the grouting cost per linear meter is reduced by approximately 12%. For strata where sampling is difficult, a method for indirectly determining the critical water content using pressure monitoring or wave velocity is provided, reducing the calibration cycle from 5-7 days to less than 1 day with a deviation of less than ±0.5%. By controlling the gelation time of the two-component grout and using a thickener combined with intermittent grouting in high-permeability strata, grout loss is effectively prevented, reducing the grouting volume by 30% and achieving the required curtain permeability coefficient. The addition of tests for the retention rate of backfill material's water immersion strength and an equal-volume fly ash substitution scheme ensures long-term water stability under different material conditions. Pre-embedded vent pipes and the use of a combination of ground-penetrating radar and core drilling ensure backfill compaction. Clearly defining the timing of secondary lining construction and the location of drainage blind ditches on the inner edge of the seepage-proof curtain avoids lining cracking and excessive drainage. In summary, this invention achieves high-quality, low-cost, environmentally friendly, and highly reliable soft rock tunnel construction.
[0016] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Detailed Implementation
[0017] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.
[0018] The proposed tunnel traverses a low mountain and hilly area with a ground elevation of 1200-1450m and a relative elevation difference of approximately 250m. The terrain is relatively vegetated, with a surface layer of 0.5-2.0m thick residual slope silty clay. The tunnel body primarily traverses interbedded layers of Lower Cretaceous argillaceous siltstone and mudstone. The rock mass exhibits a thin- to medium-thick layered structure, cemented by argillaceous material, with well-developed joints and fissures. The rock mass integrity coefficient Kv = 0.35-0.55. The natural uniaxial compressive strength of the rock is Rc = 4.5-12.0MPa, classifying it as extremely soft to soft rock. The rock mass has a high clay mineral content (illite and montmorillonite content approximately 30%-45%), making it prone to softening and disintegration upon contact with water. The groundwater type is mainly bedrock fissure water, recharged by atmospheric precipitation and lateral runoff. During the exploration, the measured borehole water level was 6-15m deep, the volumetric water content of the surrounding rock was ω=18%~32%, and the permeability coefficient was K=5×10. -6 ~8×10 -5 cm / s. The middle section of the tunnel crosses a small fault fracture zone, with a width of about 8-12m, and the water content in this zone is generally ≥30%. The tunnel exit section is covered with completely weathered mudstone with a thickness of 3-8m, which is soil-like and has a water content as high as 35%-45%, and is extremely unstable when exposed to water.
[0019] The tunnel design parameters are: single-bore, two-way, two-lane, clear width 10.5m, clear height 7.1m, maximum burial depth 135m, and total length 1872m. The tunnel deformation control standards are: allowable settlement at the arch crown ≤80mm, allowable convergence at the perimeter ≤60mm; surface settlement ≤30mm. The tunnel seepage water control requirements are: no standing water behind the lining, no dripping water at the arch, and a seepage rate of ≤0.5L / (m²) on the sidewalls. 2 •d) The void filling rate between the initial support and the surrounding rock is ≥95%. Construction period requirements: 24 months, of which the tunnel excavation and initial support stages should be completed within 14 months. Environmental protection requirements: Tunnel spoil should be used primarily for roadbed filling; any remaining spoil must be utilized locally and long-distance transportation for disposal is prohibited. Safety requirements: No water inrush or mudflow should occur at the tunnel face; the maximum settlement rate of the tunnel arch should be ≤3mm / d.
[0020] This embodiment focuses on a soft rock section of a highway tunnel (mileage markers K25+380~K25+520, length 140m). The surrounding rock in this section consists of alternating layers of silty mudstone and mudstone, with a natural water content ω=20%~35%, and a water content ≥38% in local fault fracture zones. The tunnel excavation cross-section is horseshoe-shaped, with a net width of 11.2m, a net height of 8.5m, and a burial depth of 60~90m.
[0021] The soft rock tunnel construction method includes the following steps: S1. Dynamic monitoring and threshold calibration of surrounding rock moisture content: In the excavated section (K25+320~K25+380) behind the tunnel face and the unexcavated section (K25+380~K25+550) in front of the tunnel face, moisture content sensors (using FDR-100 frequency domain reflectometers) are deployed at longitudinal intervals of 8m. At each monitoring section, one probe is buried at the arch crown, left arch waist, right arch waist, left side wall, and right side wall, at a depth of 2.0m. Continuous monitoring is carried out using the time domain reflectometer method, with data acquisition frequency of once per hour, and the data is automatically uploaded to the construction monitoring platform.
[0022] Three sets of undisturbed soft rock cores were collected on-site, and permeability and free expansion rate tests were conducted under different water contents (15%, 20%, 25%, 30%, 35%, and 40%). Test results: When the water content ω = 24%, the permeability coefficient K = 9.5 × 10⁻⁶. -6 cm / s (close to 1×10) -5 cm / s); when ω=26%, K=1.3×10 -5 cm / s, free expansion rate δ=5.2%. With K≥1×10 -5 The minimum moisture content corresponding to cm / s or δ≥5% is taken as ω. c Determine the critical moisture content ω c =25%.
[0023] S2. Advanced curtain grouting based on moisture content classification: When construction reached point K25+415, monitoring data showed that the surrounding rock above the arch crown had an ω=31% > ω c The tunnel was determined to be in a high water content state, and the second grouting mode (seepage-proof curtain) was implemented. YT-28 pneumatic drills were used to drill 42 pre-drilled small guide pipes radially along the tunnel at a 12° outward angle. The guide pipes were 4m long and spaced 1.0m circumferentially. The grouting material was a cement-water glass dual-liquid grout: ordinary Portland cement (PO42.5) was prepared with a water-cement ratio of 0.9:1; the water glass used was sodium-based water glass with a modulus of 2.8 and a Baume degree of 35°Bé. The volume ratio of cement grout to water glass grout was controlled at 1:0.7, and the grouting pressure was gradually increased from an initial 0.5MPa to 1.6MPa, with a stabilization time of 3 minutes. Core sampling after grouting showed that the curtain thickness reached 3.8m and the permeability coefficient was 8.7×10⁻⁶. -7 cm / s, satisfying ≤1×10 -6 The requirement is cm / s; When construction reached point K25+460, monitoring data showed that ω=22%≤ω cThe first grouting mode (consolidation curtain) was implemented. With the small guide pipe parameters unchanged, ordinary silicate cement single-component grout (water-cement ratio 0.9:1) was injected at a pressure of 0.7~0.9 MPa, forming a consolidation curtain with a thickness of 2.8 m. Borehole wave velocity tests of the surrounding rock after grouting showed that the longitudinal wave velocity of the rock mass increased from 1800 m / s before grouting to 2350 m / s. S3. Staged excavation and initial support of the tunnel: After the pre-grouting is completed and the grout gel time (60 seconds for two-component grout, 6 hours for single-component grout) is reached, the mid-step method is used for excavation. The upper step is 4.5m high, the middle step is 3.0m high, and the lower step has a reserved invert arch. Each cycle advances 0.6m (upper step) and 0.8m (middle and lower steps). Immediately after excavation, C25 concrete (5cm thick) is sprayed, and I18 I-beam arch frames are erected (0.8m spacing), and then sprayed again to a total thickness of 25cm to form the initial support structure. S4. Waste slag is modified into controllable low-strength backfill material: The soft rock waste generated in step S3 (mainly fragments of silty mudstone and mudstone debris) was crushed using a PE-600×900 jaw crusher and passed through a 3mm square-hole sieve to obtain fine material with a particle size ≤3mm. The following mass ratios were weighed: 1000kg of waste fine material, 150kg of cement (PO42.5), 80kg of Grade II fly ash, and 15kg of early-strength water-reducing agent (FDN type). The dry materials were mixed in a forced mixer for 2 minutes, then 18% of the total solid mass of water (i.e., (1000+150+80+15)×0.18=224kg) was added, and mixing continued for 3 minutes. The slump was measured to be 95mm. The 28-day unconfined compressive strength of this mixture was 1.1MPa (average of three groups of test blocks), meeting the requirement of 0.5~1.5MPa.
[0024] S5. Backfilling behind initial support: After the initial support was completed and cured for 72 hours, the concrete strength reached 78% of the design strength (C25) according to tests on test blocks cured under the same conditions. Grouting nozzles were installed at the pre-reserved grouting holes on the initial support surface (6m longitudinal spacing, 5 in total, circumferentially at the arch crown and arch waist). Using a UB-3 type extrusion grouting pump, the controllable low-strength backfill material prepared in step S4 was injected into the voids between the support structure and the surrounding rock at a pressure of 0.25~0.35MPa. The initial valve of the PVC vent pipe (25mm inner diameter) pre-embedded in the arch crown was opened. Once grout flowed continuously and no air bubbles appeared in the grout, the valve was closed, and grouting continued until the pressure stabilized at 0.32MPa for 2 minutes. Ground-penetrating radar was used to inspect the section from K25+400 to K25+420, and the average void filling rate was 98.2%, meeting the requirement of ≥95%.
[0025] S6: Anchor bolt secondary tensioning and locking: Hollow grouting anchor bolts were drilled and installed in a quincunx pattern at 1.0m x 1.0m intervals within a 120° range at the tunnel arch crown (60° on each side of the centerline) and at the left and right arch waists. The anchor bolts were 5m long and 25mm in diameter. The drilled holes were 42mm in diameter. After installation, an initial pre-tightening force of 50kN was applied using a torque wrench. Then, M30 cement mortar (water-cement ratio 0.4:1, with 8% UEA expansion agent) was injected through the center hole of the anchor bolt at a grouting pressure of 1.2MPa. After the grout had cured for 48 hours (with test blocks reaching 92% of the M30 design strength under the same conditions), a secondary pre-tightening force of 90kN was applied, and the tail of the anchor bolt was fully welded to the I18 steel arch frame on both sides (weld height 7mm, coated with epoxy resin anti-corrosion paint).
[0026] In this embodiment, the maximum settlement of the final arch in the construction section was 42mm (<80mm), the maximum convergence around the perimeter was 35mm (<60mm), there were no voids behind the initial support, and no water seepage was observed on the lining surface. The on-site rock deformation stabilization time was shortened from 25 days using conventional methods to 12 days, the waste utilization rate reached 100%, and no safety accidents occurred.
[0027] The previous embodiment described the case where the second grouting mode was performed at K25+415 with ω=31% and the first grouting mode was performed at K25+460 with ω=22%. The following discussion addresses the case where the water content in the tunnel is near a critical value (i.e., ω and ω...). c The section with an absolute difference of ≤2% – the mileage station K25+500~K25+530 – further explains the transition grouting mode and the sensor optimization deployment method.
[0028] Before the tunnel construction reaches K25+500, the layout plan for the moisture content sensors will be adjusted as follows: The probe burial depth of each monitoring section is uniformly controlled within 2.2m of the surrounding rock surface to avoid the influence of shallow disturbance and ensure that it can reflect the true water content of the deep surrounding rock.
[0029] Because the tunnel cross-sectional area is greater than 80m² 2 The number of circumferential measuring points has been increased from the conventional four to eight. The specific locations are: arch crown, left arch shoulder, right arch shoulder, left arch waist, right arch waist, left side wall, right side wall, and center of the invert (these points will not be installed until the invert is excavated). Each measuring point uses an FDR-100 frequency domain reflectometer probe, and data is acquired every 30 minutes.
[0030] Starting from K25+500, the longitudinal monitoring interval has been shortened from 8m to 5m.
[0031] Continuous monitoring data shows that the average moisture content ω at each measuring point in section K25+500 is 24.1%–26.3%, with ω=25.8% at the arch crown, 24.6% at the left arch waist, and 26.2% at the right arch waist. The critical moisture content ω_c is 25%. The absolute value of the difference between each measuring point and ω_c is calculated: the maximum is |26.2%-25%|=1.2%, and the minimum is |24.6%-25%|=0.4%, both ≤2%. It is determined that the section has entered the transition zone, and the transition grouting mode is executed.
[0032] For the entire section from K25+500 to K25+530 (30m in length), advanced curtain grouting will be implemented using the transition grouting mode. YT-28 pneumatic drills were used to drill small guide pipes radially along the tunnel at a 12° outward insertion angle. The circumferential spacing in the conventional mode (first or second mode) was 1.0m, but in this transitional mode, it was increased to 0.7m as required. The number of small guide pipes in each cycle (every 5m is a grouting section) increased from the original 42 to 60. The length of the small guide pipes remained 4m, and 6mm diameter overflow holes were drilled into the pipe walls, spaced 15cm apart in a quincunx pattern.
[0033] A cement-water glass dual-component grout was injected. The cement used was PO42.5 ordinary Portland cement, prepared with a water-cement ratio of 0.9:1. The water glass used had a modulus of 2.8 and a Baume degree of 35°Bé. As specified, the volume ratio of cement grout to water glass grout was 1:0.5. Compared to the second grouting mode (volume ratio 1:0.6~1:0.8), this transitional mode reduced the proportion of water glass, resulting in a moderately extended gel time (measured gel time approximately 110 seconds), thus balancing the dual requirements of consolidation and seepage prevention.
[0034] The grouting pressure range for the first grouting mode is 0.5~1.0MPa, and for the second grouting mode it is 1.0~1.8MPa. In this embodiment, the commonly used pressure for the first mode is 0.8MPa, and for the second mode it is 1.5MPa, with an average value of (0.8+1.5) / 2=1.15MPa. During construction, the initial grouting pressure is 0.5MPa, gradually increased to 1.15MPa, and stabilized for 3 minutes. The final pressure fluctuation at the end of grouting is controlled between 1.10~1.20MPa.
[0035] After the transition grouting was completed, core samples were drilled at K25+515. Observation of the core samples revealed that the surrounding rock fissures were effectively filled with grout, with grout vein widths of 1-3 mm and a permeability coefficient of 3.5 × 10⁻⁶. -6 The velocity of the surrounding rock is between the typical values of the first mode (consolidation type) and the second mode (seepage prevention type), which meets the actual requirements of the transition section for "both seepage prevention and consolidation". At the same time, the longitudinal wave velocity of the surrounding rock increases from 1850m / s to 2250m / s after grouting.
[0036] After the transition grouting was completed in the K25+500~K25+530 section, the subsequent steps S3 (step-by-step excavation and initial support), S4 (slag improvement), S5 (backfilling), and S6 (secondary tensioning and locking of anchor bolts) were all performed in the same manner as in the previous embodiment without any adjustments. Actual monitoring data showed that the maximum settlement of the arch crown after excavation of this transition section was 38mm, the maximum settlement around the perimeter was 31mm, there were no voids behind the initial support, and no water seepage or local collapse occurred, indicating good construction results.
[0037] By adopting a transitional grouting mode, in surrounding rock with a water content near the critical value (between 24% and 26%), the first mode (single-liquid grout) was not used due to insufficient consolidation leading to water seepage, and the second mode (high-cost two-liquid grout) was not used due to excessive seepage prevention resulting in material waste. Compared with adjacent sections using the single mode, the grouting cost per linear meter of the transitional section was reduced by approximately 12%, while the surrounding rock deformation control effect met the design requirements, verifying the scientific validity and practicality of the above technical parameters.
[0038] In another embodiment, when it is difficult to obtain undisturbed soft rock core samples or when the disturbance is too great, ω is indirectly determined by using a pressure-side test or in-hole wave velocity test. c ω is defined as the moisture content corresponding to when the lateral pressure modulus E0 decreases to 60% of its natural state. c Or with shear wave velocity V x The moisture content that decreases to 70% of its natural state is taken as ω. c .
[0039] In actual soft rock tunnel engineering, it is common to encounter situations where undisturbed core sampling is difficult or excessive disturbance occurs. This embodiment provides clear definition criteria: when using a dual-tube single-action core drilling method, if the core recovery rate is less than 60% within three consecutive runs, or the core is fragmented, muddy, or sandy and cannot form a complete column; or although a columnar core is obtained, the core surface shows spiral scratches, dense transverse cracks, or naturally cracks, softens, or muddies within 24 hours after extraction, or even completely disintegrates after immersion in water; or if the measured water content deviates from the in-situ true value by more than ±5% due to soaking in drilling flushing fluid and stress release, it can be considered that sampling is difficult or excessive disturbance occurs. In such cases, if conventional core sampling laboratory tests are still forcibly used to determine the critical water content ω, it will be considered difficult to obtain a core. c Not only is it costly (requiring special processes such as triple tubes and frozen core sampling, with a success rate often below 50%), but distorted test results can directly lead to errors in subsequent grouting decisions (e.g., ω). c When the volume is too high, a single-component grout should have been injected instead of a double-component grout, causing a seepage accident.
[0040] Therefore, this method provides an indirect determination of ω based on in-situ testing. cThe proposed method involves conducting pressure meter tests and in-hole shear wave velocity tests at the tunnel site or on the tunnel wall sidewalls to obtain the pressure meter modulus E0 and shear wave velocity V under different moisture contents. x Then, the moisture content corresponding to when the lateral pressure modulus E0 decreases to 60% of the natural state (i.e., undisturbed, natural moisture content state) is taken as ω. c Or with shear wave velocity V x The moisture content that decreases to 70% of its natural state is taken as ω. c .
[0041] The reason for choosing these two mechanical parameters is that the water content of soft rock is related to E0 and V. x There is a significant negative correlation between these parameters: as water content increases, clay minerals in soft rock absorb water and swell, weakening interparticle cementation, leading to an exponential or linear decrease in rock mass stiffness and strength parameters. Extensive indoor and field tests show that when E0 decreases to 60% of its natural state, the rock mass enters a significant plastic deformation stage, its self-stabilizing capacity decreases dramatically, and it is highly susceptible to excessive convergence or collapse. This mechanical inflection point coincides with the conventional permeability test (K≥1×10⁻⁶). -5 ω determined by (cm / s) or free expansion test (δ≥5%) c Highly consistent (error typically ≤ ±2%). Similarly, shear wave velocity V x A 30% decrease means that the dynamic shear modulus of the rock mass decreases by about 50%, which corresponds to the critical threshold for the transformation of the rock mass structure from "intact" to "fragmented".
[0042] This in-situ indirect measurement method has significant engineering advantages: First, it completely avoids systematic errors caused by sampling disturbances, and the data more accurately reflects the hydrological and mechanical state of the surrounding rock in situ; second, the pressuremeter test takes about 2 hours per point and the wave velocity test takes about 30 minutes, allowing for the completion of tests on multiple sections within one day. This significantly shortens the exploration cycle compared to conventional core sampling laboratory tests (which require 5-7 days), meeting the requirements for dynamic adjustment of ω during rapid tunnel construction. c The requirements are met; secondly, the testing cost is low and the success rate is high (close to 100%), especially suitable for strata that are extremely difficult to cored, such as completely weathered and fault fracture zones; finally, through field comparison and verification, in a soft rock tunnel test section, the conventional coring method measured ω c =26.3%, the pressure-side method yielded 26.8%, and the wave velocity method yielded 26.5%. The maximum deviation among the three methods was only 0.5%, far less than the allowable error in engineering (±2%). Therefore, the above scheme provides a scientific, rapid, and reliable alternative under conditions of limited sampling.
[0043] In another embodiment, in the second grouting mode of S2, the gel time of the cement-water glass dual-liquid grout is controlled between 30 and 90 seconds, achieved by adjusting the Baume degree of the water glass or by adding 0.2% to 0.5% of disodium hydrogen phosphate retarder by the mass of cement; when the permeability coefficient of the surrounding rock K ≥ 1 × 10⁻⁶ -4 When the flow rate is cm / s, 0.5% to 1.5% of calcium lignosulfonate or polyacrylamide by weight of cement is added to the two-component grout, and intermittent grouting is adopted.
[0044] In the second grouting mode (i.e., anti-seepage curtain grouting under high water content conditions), the grouting material used is cement-water glass two-component grout, and its gel time is crucial to the grouting effect. If the gel time is too short (e.g., less than 30 seconds), the grout may solidify before reaching the designed diffusion radius, leading to blockage of the grouting pipeline, a sudden increase in grouting pressure, or even failure to form a continuous and effective curtain. If the gel time is too long (e.g., greater than 90 seconds), the grout is easily diluted or washed away by groundwater in high water content surrounding rock, which not only wastes materials but also results in the grouting ring permeability coefficient not meeting the standard, thus failing to effectively prevent seepage.
[0045] Therefore, this method controls the gel time of the two-component grout within the range of 30–90 seconds, specifically through two methods: first, adjusting the Baume degree of the water glass (usually 30–40°Bé, the higher the Baume degree, the faster the gel); second, adding 0.2%–0.5% of disodium hydrogen phosphate by weight of cement as a retarder. Disodium hydrogen phosphate can form a complex with calcium ions generated during cement hydration, delaying the precipitation of calcium silicate gel, thereby precisely extending the gel time. At the construction site, the gel time needs to be checked every 20 minutes (using the inverted cup method or Vicat apparatus). If it deviates from the set range, the Baume degree of the water glass or the amount of retarder should be adjusted immediately to ensure that the grout is always in the optimal injection period during the grouting process. This technical measure ensures that the grout has sufficient time to penetrate deep into the surrounding rock fissures and can quickly solidify to form a high-strength, low-permeability seepage barrier. Core sampling at the grouting site shows that the grout vein diffusion radius is uniform, the barrier thickness meets the standard, and no pipe blockage accidents occur.
[0046] In addition, when the permeability coefficient of the surrounding rock K ≥ 1 × 10 -4 At a pressure of cm / s, the surrounding rock fissures are more developed and have better connectivity. Under high water pressure, the grout is easily lost rapidly along the large fissures, causing the "grout run" phenomenon, where the grouting pressure is difficult to increase, the grouting volume increases indefinitely, and the curtain quality decreases instead.
[0047] To address this high-permeability formation, this method employs two enhancement measures: First, 0.5%–1.5% (by weight of cement) of calcium lignosulfonate or polyacrylamide is added to the two-component grout. Calcium lignosulfonate is a common water-reducing agent and retarder, but here its main function is to increase viscosity, reduce fluidity, and thus slow the flow rate of the grout in the fissures, reducing loss. Polyacrylamide is a high-molecular-weight flocculant; even a small amount can significantly improve the cohesion and thixotropy of the grout, resulting in better "wall adhesion" and less susceptibility to being washed away. Second, the continuous grouting method is changed to an intermittent grouting process: each grouting session lasts 1–2 minutes, followed by a 0.5–1 minute pause, repeated until the grouting pressure stabilizes at the design final pressure. The principle of intermittent grouting is that during the pause, the grout begins to solidify in the fissures, forming initial strength and blocking some channels. When grouting resumes, the pressure gradually increases, forcing the grout to diffuse into smaller fissures, thereby improving the uniformity of grouting. Field practice shows that for K=1.5×10 -4 In a fault fracture zone with a fault velocity of cm / s, the above measures reduced the grouting volume per hole by approximately 30% compared to continuous grouting, while successfully increasing the grouting pressure from 0.8 MPa to 1.6 MPa. After grouting, the permeability coefficient of the surrounding rock decreased to 3.2 × 10⁻⁶. -6 The flow rate (cm / s) meets the seepage prevention requirements. Simultaneously, no grout loss occurred to the working face or surface, resulting in significant material cost savings. In summary, the aforementioned gelation time control and high-permeability grouting enhancement measures effectively resolve the contradiction between the injectability and rapid setting of the two-liquid grout, as well as the problem of grout loss in high-permeability surrounding rock. These measures are key technological supplements to ensure the successful implementation of the second grouting mode.
[0048] In another embodiment, in S4, the controllable low-strength backfill material also needs to undergo a water immersion compressive strength test: after the standard curing 28-day specimen is immersed in water for 48 hours, the unconfined compressive strength is not less than 80% of that in the dry state; if it does not meet the requirement, 5% to 10% bentonite or 2% to 4% silica fume by weight of cement is added; when fly ash is unavailable, it is replaced with an equal amount of finely ground slag powder or natural zeolite powder.
[0049] During the operation of soft rock tunnels, the groundwater environment often exists for a long time. If the backfill material loses strength significantly after being exposed to water, it may soften, be washed away, or even collapse, leading to secondary voids between the initial support and the surrounding rock. This can cause serious problems such as lining bias, cracking, or increased water leakage. Conventional waste cement-modified materials have acceptable strength under dry conditions, but their strength retention rate is often low after immersion in water (some inferior materials even have a strength retention rate of less than 50%), which cannot meet the stability requirements of the tunnel throughout its entire life cycle.
[0050] Therefore, this method adds a mandatory water stability test index to the backfill material: after the specimens have been cured for 28 days, they are immersed in water for 48 hours and their unconfined compressive strength is measured. The requirement is that it should not be less than 80% of that in the dry state.
[0051] The reason for choosing 80% as the qualified threshold is based on the statistical results of a large number of tests on soft rock tunnel backfill materials. When the strength retention rate is higher than 80%, the cement hydration products inside the material have formed a relatively stable skeleton structure with fewer capillary pores and interconnected pores, which can effectively resist the softening effect of water. Conversely, if it is lower than 80%, it indicates that the cementitious components in the material are insufficient or the porosity is too high. Under long-term immersion in water, the strength will continue to deteriorate, and eventually lose the load-bearing and force-transferring functions.
[0052] During on-site inspection, if the water immersion strength retention rate is found to be less than 80%, remedial measures are taken: 5%–10% bentonite or 2%–4% silica fume (by weight of cement) is added to the mixture. Bentonite has water absorption, expansion, and ion exchange properties, which can fill the internal pores of the material, improving density and impermeability. Its thixotropic properties also help improve pumpability; however, the dosage should not exceed 10%, otherwise excessive expansion will reduce strength. Silica fume is a highly reactive pozzolanic material; its micro-aggregate filling effect and pozzolanic reaction can significantly reduce the total porosity of the material and refine the pore size, making the hardened body more dense and thus improving water erosion resistance. After adding these two materials, the water immersion strength retention rate can usually be increased to 85%–92%, fully meeting the design requirements.
[0053] On the other hand, fly ash, as an important component of this backfill material, mainly plays the role of improving workability, reducing heat of hydration, and improving later strength and durability. However, in some remote tunnel projects, fly ash may be in short supply or of unstable quality (e.g., excessive fineness or excessive loss on ignition).
[0054] To address this practical problem, this method provides an equivalent substitution solution: when fly ash is unavailable, finely ground slag powder or natural zeolite powder can be used as a substitute, with a substitution ratio of 100% of the fly ash mass. Finely ground slag powder has a higher activity index than fly ash, which can improve early strength. Furthermore, its large specific surface area and significant filling effect, when used in this backfill material, can slightly increase the 28-day compressive strength (approximately 5%~10%), while maintaining a water immersion strength retention rate of over 80%. Natural zeolite powder has strong adsorption and ion exchange capabilities, which can fix calcium hydroxide produced during cement hydration and reduce calcium ion leaching, thereby improving the material's corrosion resistance and long-term stability.
[0055] It should be noted that when using slag powder or zeolite powder as a substitute, the water content of the mixture may need to be slightly adjusted (usually by 2% to 5%). The optimal water content should be determined through on-site slump tests to ensure that the pumpability of the backfill material is not affected. In actual engineering applications, after supplementary measures were adopted, random sampling tests on a soft rock tunnel section showed that the water immersion strength retention rate was only 72% without bentonite, but increased to 88% after adding 8% bentonite. In another section, due to the interruption of fly ash supply, finely ground slag powder was used instead, and the 28-day compressive strength of the backfill material reached 1.3 MPa (the original design requirement was 0.8 MPa), with a water immersion retention rate of 86%. On-site drilling observations showed no signs of softening or voids.
[0056] It is evident that water stability testing and remedial measures, along with fly ash alternatives, jointly ensure the long-term performance reliability and construction adaptability of backfill materials under different regions and supply conditions.
[0057] In another embodiment, in S5, PVC exhaust pipes with an inner diameter of 20-30mm are pre-embedded at the arch top and the two sides of the arch waist of the initial support structure, and ball valves are installed at the outlet end; when backfilling and grouting, the valves are opened first, and after grouting is continuously discharged without air bubbles, the valves are closed and grouting continues until the pressure is stable; the filling rate is detected by core drilling or ground-penetrating radar, and a detection section is set every 10-20m. If the core sample shows complete backfill material without continuous voids, or the porosity calculated by the ground-penetrating radar reflected wave amplitude is ≤5%, it is considered qualified.
[0058] A common and challenging problem during the backfilling grouting process behind the initial support is insufficient venting at the crown and waist of the arch. Because air is easily trapped at the highest point of the arch crown during grouting, even if the grouting pressure reaches the design value, air pockets or voids may remain in the crown if venting is inadequate, resulting in insufficient void filling. Engineering practice shows that in ordinary grouting processes without dedicated venting pipes, the incidence of voids in the arch crown is as high as 20%–30%. The presence of voids prevents the effective transfer of the surrounding rock load to the support structure, easily leading to lining cracking, spalling, or even collapse accidents later on.
[0059] Therefore, in this method, during the initial support construction, PVC vent pipes with an inner diameter of 20-30mm are pre-installed at the arch crown and both sides of the arch waist, with ball valves installed at the outlet ends. The inner diameter of the vent pipe should not be too small (less than 20mm is easily blocked by grout) nor too large (greater than 30mm will weaken the local strength of the support structure). In this embodiment, an inner diameter of 25mm is used. The function of the ball valve is to keep it open at the beginning of grouting, so that the air in the voids and the pilot grout can be smoothly discharged; when it is observed that grout is continuously discharged from the vent pipe and there are no air bubbles in the grout, it indicates that the air has been basically discharged. At this time, the ball valve is closed, so that the grouting pressure can effectively act on the entire void space and compact the backfill material to a void-free state.
[0060] On the other hand, after the backfill grouting is completed, its filling effect needs to be reliably tested to confirm whether it meets the requirement of "void filling rate ≥ 95%".
[0061] This method provides two complementary detection techniques: core drilling and ground-penetrating radar.
[0062] Core drilling is a traditional and intuitive method. The specific operation involves setting up a test section every 10-20m along the tunnel's longitudinal direction (15m in this example). At each section, five holes are drilled at the arch crown, left and right arch waists, and left and right sidewalls, with a hole diameter of 40-50mm. The holes are drilled to a certain depth (usually 30-50cm) into the initial support and backfill material behind it, and the extracted core samples are observed. If continuous and complete backfill material is visible in the core sample, and the surface of the core sample has no continuous voids or obvious cracks, then the filling at that point is considered qualified; conversely, if the core sample is broken, missing, or has obvious cavities, additional grouting is required. The advantage of this method is that the results are intuitive and do not require complex instruments. The disadvantage is that it is a destructive test and can only reflect local point-like information.
[0063] Ground-penetrating radar (GPR) is a non-destructive testing technique. It involves emitting high-frequency electromagnetic waves onto the initial support surface and receiving the reflected signals. The porosity is calculated based on the amplitude, phase, and frequency changes of the reflected waves. When the backfill is dense, the amplitude of the radar reflected waves is small and uniform; when voids exist, strong reflected waves are generated at the void interface, significantly increasing the amplitude. This method requires a porosity ≤5% to be considered acceptable. This threshold corresponds to a 95% fill rate and is consistent with engineering experience that voids accounting for no more than 5% of the tunnel area will not cause lining defects. The advantages of GPR are its speed, comprehensiveness, and continuous scanning capability across the entire tunnel, enabling the detection of localized voids that are easily missed during core sampling. However, it requires highly experienced operators and needs to be calibrated and verified in conjunction with core sampling.
[0064] Therefore, in practice, it is recommended to use the two methods in combination: first, use ground-penetrating radar to conduct a rapid survey of the entire cross section, and then use core drilling to accurately verify suspected cavity areas. The two methods corroborate each other to ensure the accuracy and reliability of the detection results.
[0065] In another embodiment, in S6, 8% to 12% of UEA expansion agent or 5% to 8% of aluminum powder paste by weight of cement is added to M30 cement mortar to control the volume expansion rate at 0.02% to 0.05%; when welding the tail of the anchor rod to the steel arch frame, a 10cm long thick-walled steel pipe reinforcing sleeve is first fitted, and after the reinforcing sleeve is threadedly connected to the anchor rod, it is fully welded to the steel arch frame on both sides, with a weld height ≥6mm, and anti-corrosion treatment is performed.
[0066] During the secondary tensioning and locking process of anchor bolts, the quality of the anchor bolt grouting material and the connection between the anchor bolt tail and the steel arch directly determines whether the preload can be effectively transmitted and maintained in the long term. Firstly, after the hollow grouting anchor bolt is installed, M30 cement mortar needs to be injected into the annular gap between the anchor bolt and the borehole wall to anchor the anchor bolt and transfer the load to the depths of the surrounding rock. However, ordinary cement mortar shrinks during the hardening process (both auto-shrinkage and drying shrinkage), with a shrinkage rate typically between 0.04% and 0.10%. This leads to micro-cracks at the bonding interface between the mortar and the borehole wall and the anchor bolt, and even voids at the top of the anchor bolt. Consequently, the subsequently applied secondary preload cannot be effectively transmitted to the surrounding rock, resulting in a preload loss rate of 30% to 50%.
[0067] To address this issue, this method involves adding 8%–12% UEA expanding agent or 5%–8% aluminum powder paste (by weight of cement) to M30 cement mortar. The UEA expanding agent (calcium sulfoaluminate) reacts with cement hydration products to form ettringite, resulting in volume expansion. The aluminum powder paste undergoes a hydrogen evolution reaction in an alkaline environment, forming tiny, uniform bubbles that cause slight expansion of the mortar. By controlling the dosage, the volume expansion rate of the mortar is maintained between 0.02% and 0.05%.
[0068] This range was chosen for the following reasons: when the expansion rate is below 0.02%, it is difficult to compensate for shrinkage, and micro-cracks still exist at the bonding interface; when the expansion rate is above 0.05%, excessive expansion pressure may lead to local cracking of the surrounding rock or excessive stress in the anchor sleeve, which would weaken the anchoring effect. Actual tests show that after adding 10% UEA expansion agent, the 28-day restricted expansion rate of the mortar is 0.035%, and the anchor pull-out test shows that the preload loss rate decreased from the original 42% to 8%, and the bond strength between the anchor and the surrounding rock increased by about 25%.
[0069] Secondly, the tail of the anchor bolt needs to be welded and fixed to the I-beam arch of the initial support to form a joint load-bearing system of "surrounding rock-anchor bolt-steel frame". However, the conventional method of directly welding the tail of the anchor bolt to the steel arch has two weak points: First, the tail of the anchor bolt is usually a solid threaded end, with a small contact area with the flange of the steel arch and a limited weld length. Under high preload and surrounding rock deformation loads, the weld is prone to tearing or the anchor bolt is pulled out from the weld. Second, the heat-affected zone of the weld will reduce the mechanical properties of the anchor bolt steel, and the weld is prone to corrosion, resulting in a decrease in long-term durability.
[0070] Therefore, this method first fits a 10cm thick-walled steel pipe reinforcing sleeve on the tail of the anchor rod. The inner diameter of the reinforcing sleeve matches the outer diameter of the tail of the anchor rod, and the two are connected by threads (the inner wall of the reinforcing sleeve is tapped, and the tail of the anchor rod has a pre-set external thread), so that the reinforcing sleeve becomes the extended stress section of the anchor rod.
[0071] The 10cm length of the reinforcing sleeve was determined through optimization: too short (<5cm) would result in insufficient weld length, while too long (>15cm) would occupy tunnel clearance and hinder construction. The reinforcing sleeve and steel arch frame are joined using double-sided full welding, with a weld height of no less than 6mm. Compared to single-sided or intermittent welding, double-sided full welding doubles the effective cross-sectional area of the weld, significantly improving load-bearing capacity and resulting in a more uniform stress distribution. The 6mm weld height, according to steel structure design specifications, provides sufficient shear and tensile strength for steel with a thickness of 8-12mm, while avoiding excessive heat input that could damage the base material. After welding, the weld and heat-affected zone are treated with anti-corrosion measures (such as applying epoxy zinc-rich paint or wrapping with anti-corrosion tape) to prevent electrochemical corrosion from groundwater and in humid environments.
[0072] The on-site comparison results show that after adopting the reinforcing sleeve and double-sided full welding process, the tensile bearing capacity of the anchor bolt tail weld increased from about 45kN of conventional single-sided welding to 92kN, and the failure mode changed from weld tearing to anchor bolt base material yielding, indicating that the connection strength is higher than that of the anchor bolt itself; under the same design preload (90kN), no visible deformation or cracking occurred at the weld.
[0073] Therefore, the micro-expansion mortar and reinforcing sleeve welding technology, starting from the two key nodes of the anchor bolt, namely the "anchoring end" and the "locking end", significantly improve the long-term reliability of the anchor bolt secondary tensioning and locking system.
[0074] In another embodiment, the soft rock tunnel construction method further includes: S7. After the anchor bolts are locked with secondary pre-tightening force, and the tunnel deformation monitoring shows that the arch settlement rate is <0.2mm / day for 5 consecutive days and the perimeter convergence rate is <0.1mm / day for 5 consecutive days, the secondary lining shall be constructed with concrete strength ≥C30 and thickness ≥30cm. Before construction, longitudinal drainage blind ditches shall be set at the foot of the walls on both sides of the tunnel, and transverse drainage pipes shall be set every 10m. The drainage blind ditches shall be located at the inner edge of the anti-seepage curtain grouting ring.
[0075] After the anchor bolts are pre-tightened and locked, the tunnel construction enters the secondary lining construction stage. The timing of the secondary lining construction is crucial: if it is constructed too early, the surrounding rock has not fully released its deformation, and the secondary lining will be subjected to excessive deformation pressure, which may lead to cracking of the lining; if it is constructed too late, the deformation of the surrounding rock may be too large, exceeding the design allowance, or even causing instability and collapse.
[0076] The specific criteria for implementation in this method are: the crown settlement rate must be less than 0.2 mm / day for five consecutive days, and the peripheral convergence rate must be less than 0.1 mm / day for five consecutive days. These two values are determined based on statistical analysis of a large amount of soft rock tunnel deformation monitoring data. Soft rock tunnel deformation typically goes through three stages: a rapid deformation period (rate > 1 mm / day), a slow deformation period (rate 0.2~1 mm / day), and a basically stable period (rate < 0.2 mm / day). When the crown settlement rate is less than 0.2 mm / day for five consecutive days, it indicates that the surrounding rock has entered a basically stable period, and approximately 90% of the deformation has been released. The peripheral convergence rate is even smaller than the crown settlement rate (taken as 0.1 mm / day) because the horizontal convergence of soft rock tunnels tends to decay faster than vertical settlement; this indicator helps prevent the secondary lining from being subjected to excessive horizontal compression. The five-day observation period eliminates the influence of occasional daily fluctuations.
[0077] After this condition is met, secondary lining is constructed. This ensures that the lining thickness (not less than 30cm) and strength (not less than C30) meet the structural safety requirements. It also allows the lining to serve primarily as a safety reserve and waterproof layer after the surrounding rock stabilizes, rather than as a load-bearing structure, thereby extending the tunnel's service life.
[0078] On the other hand, the coordination between the drainage system and the advanced grouting curtain during the operation of soft rock tunnels is often overlooked, leading to drainage structure failure or curtain damage.
[0079] Before the secondary lining is constructed, longitudinal drainage blind ditches are installed at the base of the walls on both sides of the tunnel, covered with geotextile to prevent clogging by mud and sand. A transverse drainage pipe is installed every 10m to introduce water into the central drainage ditch of the tunnel. At the same time, the drainage blind ditches must be located on the inner edge of the anti-seepage curtain grouting ring.
[0080] The principle behind this location selection is as follows: the seepage-proof curtain grouting ring is a low-permeability layer (permeability coefficient ≤ 1×10⁻⁶) formed in high-water-content surrounding rock using two-component grout. -6 The drainage ditch (cm / s) serves to prevent groundwater from seeping into the tunnel. If the drainage ditch is placed outside the curtain ring, it will intercept groundwater that should be blocked by the curtain, leading to excessive drainage volume, long-term siltation and blockage, and potentially causing a decrease in the water head outside the curtain, rendering it ineffective. If the drainage ditch is placed too far inside the curtain ring, water pressure may accumulate between the surrounding rock and the lining. When the water pressure exceeds the lining's bearing capacity, leakage or even damage may occur. Placing the drainage ditch on the inner edge of the curtain ring means that it directly collects the small amount of seepage water passing through the curtain or residual groundwater in the surrounding rock fissures, resulting in the shortest drainage path, the lowest water pressure, and no impact on the hydrological balance outside the curtain. Horizontal drainage pipes are installed every 10m with appropriate spacing to ensure smooth drainage while avoiding excessive cutting of the initial support structure.
[0081] During on-site implementation, the actual boundary of the anti-seepage curtain ring is first determined by drilling or ground-penetrating radar (based on grouting core sampling or resistivity methods). Then, a longitudinal blind ditch is installed approximately 5-10 cm from the inner side of the curtain ring, ensuring that the blind ditch neither penetrates nor deviates too far from the curtain ring. By precisely controlling the timing of secondary lining construction and scientifically arranging the drainage system, the synergistic optimization of surrounding rock stability control, structural safety, and groundwater balance is achieved.
[0082] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and embodiments shown and described herein.
Claims
1. A method for constructing soft rock tunnels, characterized in that, Includes the following steps: S1. In the surrounding rock of the excavated section behind the tunnel face and the unexcavated section in front, moisture content sensors are installed at longitudinal intervals of 5-10m. The volumetric moisture content ω of the surrounding rock is continuously monitored using the time-domain reflectometry method. Uncirculated soft rock cores are taken from the tunnel site to conduct permeability and expansion tests under different moisture content conditions, with the surrounding rock permeability coefficient K≥1×10⁻⁶. -5 The minimum moisture content corresponding to a free expansion rate δ ≥ 5% is taken as the critical moisture content ω. c If sufficient rock cores cannot be obtained on site, then take ω. c =25% is the default value; S2, when the real-time monitored ω≤ω c When the surrounding rock is determined to be in a medium water content state, the first grouting mode is implemented: drill advanced small guide pipes with an outward insertion angle of 10°~15° along the radial direction of the tunnel. The length of the small guide pipes is 3~5m and the circumferential spacing is 0.8~1.2m. Ordinary silicate cement single-liquid grout is injected into the surrounding rock through the small guide pipes. The water-cement ratio is 0.8:1~1:1 and the grouting pressure is 0.5~1.0MPa, forming a consolidated curtain grouting ring with a thickness of not less than 2.5m. When the real-time monitored ω>ω c When the surrounding rock is determined to be in a high water content or water-rich state, the second grouting mode is executed: Similar to the first grouting mode, a pre-drilled small guide pipe is installed, but a cement-water glass dual-liquid grout is injected. The water-cement ratio of the cement grout is 0.8:1~1:1, the Baume degree of the water glass grout is 30~40°Bé, the volume ratio of cement grout to water glass grout is 1:0.6~1:0.8, and the grouting pressure is 1.0~1.8MPa, forming a seepage-proof curtain grouting ring with a thickness of not less than 3.5m, and the permeability coefficient of this seepage-proof curtain grouting ring is ≤1×10⁻⁶. -6 cm / s; S3. After the pre-curtain grouting is completed and the grout gel time reaches the set value, the tunnel is excavated in stages using the step method, with each cycle advancing ≤0.8m; immediately after excavation, C25 grade or higher concrete is sprayed and I-beam arch frames are erected to form the initial support structure. S4. Crush and screen the soft rock waste generated in step S3 to a particle size ≤3mm; mix it according to the mass ratio of waste:cement:fly ash:early strength water-reducing agent = 1:(0.12~0.18):(0.05~0.10):(0.01~0.02), and add 15%~20% water of the total solid mass, and stir until the slump is 80~120mm to obtain a controllable low strength backfill material with a 28-day unconfined compressive strength of 0.5~1.5Mpa; S5. After the initial support structure is completed and reaches more than 70% of the design strength, reserve or drill backfill grouting holes on the surface of the initial support. Inject the controllable low-strength backfill material obtained in step S4 into the gap between the initial support structure and the surrounding rock through grouting equipment at a pressure of 0.2~0.4MPa until grout continuously flows out of the vent hole and the grouting pressure is stable at more than 0.3MPa for 2 minutes. Stop grouting to make the gap filling rate ≥95%. S6: Hollow grouting anchors are drilled and installed within a 120° range of the tunnel arch and at the waist positions on both sides. The anchors are 4-6m long and spaced 1.0m x 1.0m apart. After the anchors are inserted into the surrounding rock, an initial pre-tightening force of 50kN is applied. Then, M30 cement mortar is injected through the center hole of the anchor at a grouting pressure of 1.0-1.5MPa. After the grout reaches the design strength, a second pre-tightening force is applied to the anchors to make the final pre-tightening force reach 80-100kN. The tail of the anchor is then welded and fixed to the steel arch frame of the initial support.
2. The soft rock tunnel construction method as described in claim 1, characterized in that, In S2, when the real-time monitored ω and ω c When the absolute value of the difference is ≤2%, a transitional grouting mode is implemented: the circumferential spacing of the advanced small guide pipes is increased to 0.6~0.8m, and cement-water glass double-liquid grout with a volume ratio of 1:0.5 is injected. The grouting pressure is taken as the average value of the first and second grouting modes; the water content sensor is buried at a depth of 1.5~3.0m within the surface of the surrounding rock, with no less than 4 measuring points evenly arranged circumferentially; for cross-sectional areas >80m² 2 For large-section tunnels, the longitudinal monitoring interval is 5m, and the number of circumferential monitoring points is increased to 8.
3. The soft rock tunnel construction method as described in claim 1, characterized in that, When it is difficult to obtain undisturbed soft rock core samples or when the disturbance is too great, the ω can be indirectly determined by pressure meter tests or borehole wave velocity tests. c ω is defined as the moisture content corresponding to when the lateral pressure modulus E0 decreases to 60% of its natural state. c Or with shear wave velocity V x The moisture content that decreases to 70% of its natural state is taken as ω. c .
4. The soft rock tunnel construction method as described in claim 1, characterized in that, In the second grouting mode of S2, the gel time of the cement-water glass dual-liquid grout is controlled between 30 and 90 seconds, which is achieved by adjusting the Baume degree of the water glass or by adding 0.2% to 0.5% of disodium hydrogen phosphate retarder by the mass of cement; when the permeability coefficient of the surrounding rock K ≥ 1 × 10 -4 When the flow rate is cm / s, 0.5% to 1.5% of calcium lignosulfonate or polyacrylamide by weight of cement is added to the two-component grout, and intermittent grouting is adopted.
5. The soft rock tunnel construction method as described in claim 1, characterized in that, In S4, controllable low-strength backfill materials also need to undergo water immersion compressive strength testing: after standard curing for 28 days, the unconfined compressive strength of the specimens should not be less than 80% of that in the dry state after immersion in water for 48 hours; if this is not met, 5% to 10% bentonite or 2% to 4% silica fume should be added according to the cement mass; when fly ash is unavailable, it should be replaced with an equal amount of finely ground slag powder or natural zeolite powder.
6. The soft rock tunnel construction method as described in claim 1, characterized in that, In S5, PVC exhaust pipes with an inner diameter of 20~30mm are pre-embedded at the arch top and the two sides of the arch waist of the initial support structure, and ball valves are installed at the outlet end. When backfilling and grouting, the valve is opened first, and after grouting is continuously discharged without air bubbles, the valve is closed and grouting is continued until the pressure is stable. The filling rate is tested by core drilling or ground-penetrating radar. A test section is set every 10~20m. If the core sample shows complete backfill material without continuous voids, or the porosity calculated by the ground-penetrating radar reflected wave amplitude is ≤5%, it is considered qualified.
7. The soft rock tunnel construction method as described in claim 1, characterized in that, In S6, 8%~12% of UEA expansion agent or 5%~8% of aluminum powder paste by weight of cement is added to M30 cement mortar to control the volume expansion rate at 0.02%~0.05%. When welding the tail of the anchor rod to the steel arch frame, a 10cm long thick-walled steel pipe reinforcing sleeve is first fitted. After the reinforcing sleeve is threaded to the anchor rod, it is fully welded to the steel arch frame on both sides. The weld height is ≥6mm and anti-corrosion treatment is performed.
8. The soft rock tunnel construction method as described in claim 1, characterized in that, Also includes: S7. After the anchor bolts are locked with secondary pre-tightening force, and the tunnel deformation monitoring shows that the arch settlement rate is <0.2mm / day for 5 consecutive days and the perimeter convergence rate is <0.1mm / day for 5 consecutive days, the secondary lining shall be constructed with concrete strength ≥C30 and thickness ≥30cm. Before construction, longitudinal drainage blind ditches shall be set at the foot of the walls on both sides of the tunnel, and transverse drainage pipes shall be set every 10m. The drainage blind ditches shall be located at the inner edge of the anti-seepage curtain grouting ring.